Islamic Welfare System as a Preference to Support Economic Development: A Panacea to the Welfare Challenges in North East Nigeria - Muhammad Kabiru Sabo; Muhammad Hamma `Adama Ahmad (Minhaj International Journal of Economics and Organization Sciences, 2024)
The harmful fallacy in capitalist economy is the payment of usury “interest” that plays uncalled-for role in the system, which is based on exploitation, uncontrolled profit making, misappropriation of public funds, and increasing socio-economic inequality, which becomes the main feature of a democratic system of governance, the living conditions of the average citizen continuous to decline in North East Nigeria, this motivated the writing of this paper. Islamic welfare system encompasses human wellbeing, fostering of good life to all livings, nurturing a climate of love and affection. The article is geared to answer the question, how is the welfare system in Islam seen in the context of contemporary welfare challenges in North East of Nigeria? The article aims to examine the welfare system in Islam as seen in the context of contemporary welfare challenges. The paper is positional in nature. The Methodology used in developing this paper is based on consultation of literature related to the subject matter. The paper find that the living condition and welfare of the people is the prey, and the living conditions of the average citizen continue to decline. The paper recommendes that governments ought to set up principles of socio-economic justice in the distribution of income and wealth; for the welfare of Muslims` Community. It concludes that Muslims should always manifest and advocate the practice of donations and feedings, voluntary expenditure, as well as Al-Waqf endowment for the benefits of masses. Islamic Welfare, Socio-Economic Justice